(EVALUASI PEMBELAJARAN MENGGUNAKAN APLIKASI ZOOM CLOUD MEETING PADA MAHASISWA PRODI PAI FAKULTAS TARBIYAH DAN KEGURUAN UNIVERSITAS ISLAM KUANTAN SINGINGI ( TA 2021/2022) - Zulhendra Zulhendra; Zulhaini Zulhaini; Ikrima Mailani (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2023)
This study is a qualitative research, the subjects in this study were 67 PAI study study students from semesters 2, 4, and 6, the object in this study was the Evaluation of the CIPP Model towards learning using the Zoom Cloud Meeting application for students of the Islamic Religious Education Study Program Faculty Tarbiyah and Teacher Training at the Islamic University of Kuantan Singingi (FY 2021/2022), collecting data using interviews and documentation, while data analysis techniques use data reduction, data display, data triangulation, and conclusions.The results of this study can be seen from the results of the analysis of interview data and documentation as follows, 1) Based on the evaluation of the context component, that the implementation of learning using the Zoom Cloud Meeting application is due to government regulations regarding the prevention and handling of the COVID-19 outbreak which requires learning from home, 2) Based on the evaluation of the input component, it shows that the facilities used by students to carry out learning using the Zoom Cloud Meeting application are adequate, 3) based on the evaluation of the process components, in the learning process the average student is able to use the Zoom Cloud Meeting application in learning but there are network problems that are felt by students in various regions, especially if the electricity goes out or the weather is bad, the worst possibility is that students cannot take part in learning , and if the network is not good, students can go in and out of the zoom class and cause a lack of enthusiasm for learning.